1993
DOI: 10.1080/01630569308816541
|View full text |Cite
|
Sign up to set email alerts
|

New effective moduli of uniqueness and uniform a priori estimates for constants of strong unicity by logical analysis of known proofs in best approximation theory

Abstract: Let U and V be complete separable metric spaces, Vu compact in V and G : U × V → IR a continuous function. For a large class of (usually non-constructive) proofs of uniqueness theoremsone can extract an effective modulus of uniqueness Φ by logical analysis, i.e.Since Φ does not depend on v1, v2 it is an a-priori estimate, which generalizes the notion of strong unicity in Chebycheff approximation theory. This applies to uniqueness proofs in Chebycheff approximation, · 1-approximation of f ∈ C[0, 1] and best uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…This, in particular, is the case for best approximation theory, where based on functional interpretation new results on the best Chebycheff as well as L 1 -approximation of functions in C[0, 1] by polynomials p ∈ P n of degree ≤ n (for the case of Chebycheff approximation also for more general so-called Haar spaces instead of polynomials) have been obtained ( [56,57,74]). Whereas the difficult cases of Chebycheff and L 1 -approximation deal with the special spaces C[0, 1] and P n the following much simpler uniqueness result applies to a general class of spaces.…”
Section: Extraction Of Effective Uniform Bounds In Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This, in particular, is the case for best approximation theory, where based on functional interpretation new results on the best Chebycheff as well as L 1 -approximation of functions in C[0, 1] by polynomials p ∈ P n of degree ≤ n (for the case of Chebycheff approximation also for more general so-called Haar spaces instead of polynomials) have been obtained ( [56,57,74]). Whereas the difficult cases of Chebycheff and L 1 -approximation deal with the special spaces C[0, 1] and P n the following much simpler uniqueness result applies to a general class of spaces.…”
Section: Extraction Of Effective Uniform Bounds In Analysismentioning
confidence: 99%
“…This approach, also called 'proof mining', has led to a number of new effective quantitative results but also to new qualitative results on the independence of solutions from certain parameters (uniformity results). The following papers in analysis use directly such techniques or use results obtained by these techniques or have been guided by general logical metatheorems which were established using functional interpretations: [4,10,11,12,13,14,25,57,61,62,63,65,70,71,72,73,74,88]. For surveys see [67,68] and -though covering only results up to 2002 - [74] which explains in detail general aspects of applying functional interpretation to analysis.…”
Section: Extraction Of Effective Uniform Bounds In Analysismentioning
confidence: 99%
“…The predicate 'uniform' here means that the bound Φ does not depend on v ≤ ρ tuk. In [7] we have shown, how sentences (1) naturally arise in analysis and why such uniform bounds are of numerical interest (see also [5], [6]). Proofs in analysis can be formalized in a suitable base theory T ω plus certain (in general nonconstructive) analytical principles Γ (typically not derivable in T ω ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover we gave a perspicuous method for the the extraction of bounds from proofs using WKL and arbitrary axioms (4) by a new combination of functional interpretation with majorization which, in [7], was simplified even further to the monotone functional interpretation. In [5], [6] this was applied to concrete proofs in best approximation theory yielding new numerical estimates which improved known estimates significantly (see [7] for a discussion of these results). In [5] we also gave a detailed representation of IR, C[0, 1] and more general complete separable metric spaces and showed that e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This gives functional interpretations the ability of extracting programs and other effective data 4 under certain conditions from ineffective proofs (proof mining). Monotone-functional-interpretationbased proof mining has already produced important results in computational analysis and has helped to obtain new results in mathematical analysis (see, e.g., [26,28,29,31,32,35,36,37,38]). …”
Section: Introductionmentioning
confidence: 99%